Pilot plant study of recovery of lactic acid from ethyl lactate - Barve, Prashant P.; Rahman, Imran; Kulkarni, Bhaskar D. (Organic Process Research & Development, 2009)
Purified lactic acid is used for production of biodegradable polymer. Esterification with ethanol and subsequent hydrolysis in distillation columns to produce purified lactic acid without catalyst has obvious advantages. In this paper, we present a pilot-plant study of ethyl lactate hydrolysis to produce 3.86 kg/h lactic acid (99.85% purity) using three distillation columns. Simulation of distillation columns at steady state has been carried out, and the results obtained tally with the experimental results of the pilot plant.

Purification of lactic acid via esterification of lactic acid using a packed column, followed by hydrolysis of methyl lactate using three continuously stirred tank reactors (CSTRs) in series: a continuous pilot plant study - Kamble, Sanjay P.; Barve, Prashant P.; Joshi, Jyeshtharaj B.; Rahman, Imran; Kulkarni, Bhaskar D. (Industrial & Engineering Chemistry Research, 2012)
The world market of lactic acid is growing every year, mainly as a solvent and precursor to poly(lactic acid) (PLA). The cost of renewable biomass-derived PLA will have to compete with other synthetic polymers, if it is to grab a significant and sustainable fraction of the market share. It is thus necessary to have efficient and cost-effective technology for the production of pure-grade lactic acid (LA). In this article, a novel cost-effective, eco-friendly continuous process for the production of high-quality lactic acid at pilot plant scale has been demonstrated. The novelty of this process is that, for the first time, we report and use the concept of inverse reactive distillation for the esterification of crude concentrated LA in a continuous countercurrent packed column mode. This allows us to operate the column at higher temperatures, improving the kinetic rate process and leading to shorter columns. This is followed by the hydrolysis of methyl lactate (MLA) in a series of three continuously stirred tank reactors (CSTRs), where LA itself acts as a catalyst. The LA obtained in the pilot plant process shows 99.81% purity (by weight) on water-free basis and has an optical purity of 99.9%. The pilot scale experimental results pertaining to the autocatalytic esterification of LA and hydrolysis of MLA have been compared and validated, with respect to simulated results. The innovations reported here can make the process economically viable for commercial use.